Observations on Malenchus geraerti n. sp. (Rhabditida: Tylenchidae), a morphological and molecular phylogenetic study - Pedram, Majid; Soleymanzadeh, Mahya; Pourjam, Ebrahim; Mobasseri, Mahyar (Zootaxa, 2018)
Malenchus geraerti n. sp., recovered from natural regions of northern Iran, is described and illustrated based on morphological, morphometric and molecular data. The new species is characterized by having females with a short body, an anteriorly wide S-shaped amphidial opening narrowing posteriorly, cuticle with prominent annuli, lateral field a plain band with smooth margins, muscular metacorpus with well-developed valve and corresponding plates, spermatheca filled with small spheroid sperm cells, vulva sunken in body with large epiptygma and no flap, and conical tail tapering gradually to a more or less pointed tip. Males of the new species are characterized by having a short body, tylenchoid spicules, adcloacal bursa with smooth margin and tail similar to that of the female. Morphologically, the new species is similar to five known species of the genus: M. fusiformis, M. machadoi, M. pachycephalus, M. solovjovae and M. undulatus. It most closely resembles M. pachycephalus, but as a cryptic species it can be differentiated using morphological and molecular characteristics. Comparisons with the four other aforementioned species are also discussed. Molecular phylogenetic studies using partial sequences of small and large subunit ribosomal DNA fragments reveal that the new species forms a clade with the species M. neosulcus in the small subunit (SSU) rDNA, and two species of Lelenchus in the large subunit (LSU) rDNA tree.